Biochemical and functional characterization of superoxide dismutase from the psychrophilic eubacterium Pseudoalteromonas haloplanktis - CASTELLANO, IMMACOLATA; RUOCCO, MARIA ROSARIA; DE VENDITTIS, EMMANUELE; MASULLO M (country:ITA, 2004)
Superoxide dismutase (SOD) is a metal-enzyme, catalyzing the dismutation of superoxide anion in molecular oxygen and hydrogen peroxide. It is involved in the cellular defence mechanism against the reactive and toxic products of oxygen metabolism. SODs have been classified into two main families, according to their different structural folding and metal content: the Cu/Zn family and that containing Fe or Mn in the active site. SODs isolated from extremophilic organisms are suitable models to study the structure-function relationships and the molecular and evolutive mechanisms for the adaptation of proteins to extreme environments. We have previously isolated a SOD from the hyperthermophilic archaeon Sulfolobus solfataricus (SsSOD). Its is a Fe-SOD endowed with a remarkable heat stability, its t1/2 being 2 hours at 100°C. Structural ands functional studies on the recombinant SsSOD and the analysis of some mutant and modified forms have explained several aspects about the mechanisms adopted by the enzyme to function at high temperatures. Therefore, it could be interesting to carry out similar studies also in a psychrophilic organism. In this communication we report the purification and the preliminary biochemical characterization of SOD from the psychrophilic eubacterium Pseudoalteromonas haloplanktis, isolated from Antarctic marine sediments and adapted to grow at low temperatures. SOD from P. haloplanktis (PhSOD) was purified to homogeneity from cells grown at 4°C by two chromatographic steps on a DEAE-Sepharose and HTP. The relative molecular mass of the purified enzyme, estimated by SDS-PAGE is 22,000. As SsSOD, also PhSOD shows a homotetrameric structure, as determined by gel filtration. PhSOD has a unusual thermal stability for a psychrophilic enzyme, as evaluated by its half-life of 10 min at 52°C. Similar results were obtained by UV-melting curves. The heat stability seems to be a feature possessed by a number of SODs; for instance, rat mitochondrial Mn-SOD has a a melting temperature of 87°C. Enzymatic ...